Ramucirumab combined with FOLFOX as front-line therapy for advanced esophageal, gastroesophageal junction, or gastric adenocarcinoma: a randomized, double-blind, multicenter Phase II trial - Yoon, H.H. (Ann Oncol, 2016)
This phase II trial examined the addition of ramucirumab, a vascular endothelial growth factor receptor-2 monoclonal antibody, to mFOLFOX6 as front-line therapy for patients with advanced gastric/GEJ or esophageal adenocarcinoma. A survival benefit was not observed in the ITT population, but an exploratory analysis suggested a potential benefit for ramucirumab in the gastric/GEJ cancer subgroup. BACKGROUND: We report the first randomized, Phase II trial of ramucirumab, an anti-vascular endothelial growth factor receptor-2 monoclonal antibody, as front-line therapy in patients with advanced adenocarcinoma of the esophagus or gastric/gastroesophageal junction (GEJ). PATIENTS AND METHODS: Patients from the USA with advanced esophageal, gastric, or GEJ adenocarcinoma randomly received (1:1) mFOLFOX6 plus ramucirumab (8 mg/kg) or mFOLFOX6 plus placebo every 2 weeks. The primary end point was progression-free survival (PFS) with 80% power to detect a hazard ratio (HR) of 0.71 (one-sided α = 0.15). Secondary end points included evaluation of response and overall survival (OS); an exploratory ramucirumab exposure–response analysis was undertaken. RESULTS: Of 168 randomized patients, 52% of tumors were located in the stomach/GEJ and 48% in the esophagus. The trial did not meet the primary end point of PFS [6.4 versus 6.7 months, HR 0.98 (95% confidence interval 0.69–1.37)] or the secondary end point of OS (11.7 versus 11.5 months) in the intent-to-treat (ITT) population. Objective response rates (45.2% versus 46.4%) were similar between arms. Most Grade ≥3 toxicities did not differ significantly between arms, yet premature discontinuation of FOLFOX and ramucirumab (for reasons other than progressive disease) was more common among ramucirumab- versus placebo-treated patients. In an exploratory analysis that censored for premature discontinuation, the HR for PFS favored the ramucirumab arm (HR 0.76), particularly in patients with gastric/GEJ cancer. An exploratory exposure–response analysis indicated that patients with higher ramucirumab exposure had longer OS. CONCLUSION: The addition of ramucirumab to front-line mFOLFOX6 did not improve PFS in the ITT population. CLINICALTRIALS.GOV IDENTIFIER: NCT01246960.